Calder NOW. - Buchhart, Dieter; van Diggelen, Eva; Grau, Donatien; Hofbauer, Anna Karina; van Karnebeek, Herman; Rower, Alexander S.C.; Rue, Gryphon (Rotterdam ; Tielt : Kunsthal Rotterdam : Lannoo Publishers, 2021)
Eliasson, Olafur ; Kempinas, Žilvinas ; Leigh, Simone ; Neto, Ernesto ; Nicolai, Carsten ; Sasamoto, Aki ; Signer, Roman ; Sosnowska, Monika ; Sze, Sarah ; Tiravanija, Rirkrit
Calder Now, Kunsthal Rotterdam, Rotterdam, 21 November 2021 to 29 May 2022
boek
Keywords: Calder, Alexander